1997
DOI: 10.1164/ajrccm.155.4.9105082
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory effects are associated with the number of ultrafine particles.

Abstract: The association between fine and ultrafine particles and respiratory health was studied in adults with a history of asthma in Erfurt, Eastern Germany. Twenty-seven nonsmoking asthmatics recorded their peak expiratory flow (PEF) and respiratory symptoms daily. The size distribution of ambient particles in the range of 0.01 to 2.5 microm was determined with an aerosol spectrometer during the winter season 1991-1992. Most of the particles (73%) were in the ultrafine fraction (smaller than 0.1 microm in diameter),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
572
4
17

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,105 publications
(609 citation statements)
references
References 0 publications
16
572
4
17
Order By: Relevance
“…However, exposure to fine particles in ambient air has been associated with several adverse health outcomes, including respiratory and cardiac responses (Peters et al, 1997;Von Klot et al, 2002;Penttinen et al, 2001). These health effects have shown stronger associations with the number concentrations of ultrafine particles (<0.1 μm) than with mass or number concentrations of larger particles.…”
Section: Discussionmentioning
confidence: 99%
“…However, exposure to fine particles in ambient air has been associated with several adverse health outcomes, including respiratory and cardiac responses (Peters et al, 1997;Von Klot et al, 2002;Penttinen et al, 2001). These health effects have shown stronger associations with the number concentrations of ultrafine particles (<0.1 μm) than with mass or number concentrations of larger particles.…”
Section: Discussionmentioning
confidence: 99%
“…People with asthma or chronic obstructive pulmonary disease may be particularly susceptible to the respiratory effects of UFPs, as deposition is greater in these individuals (Brown et al, 2002;Chalupa et al, 2004). Indeed, ambient UFP concentrations have been associated with a decrease in peak expiratory flow rate (Peters et al, 1997;Penttinen et al, 2001) as well as wheezing, shortness of breath, and cough in asthmatic adult populations (Von Klot et al, 2002). Similar investigations have been conducted in populations of asthmatic children (Pekkanen et al, 1997;Tiitanen et al, 1999), but separating the independent effects of different sized particles was difficult in these studies owing to their high inter-correlations.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that a large number of ultrafine particles (particles smaller than 0.1 mm) in urban air may be the explanation for the observed health effects of PM (Oberdo¨rster et al, 1995;Seaton et al, 1995). The adverse effect of ultrafine particles on respiratory symptoms, lung function and daily cardiopulmonary mortality has been discussed in several studies (Peters et al, 1997;Penttinen et al, 2001).…”
Section: Introductionmentioning
confidence: 99%